MESSAGE FROM THE PLENARY PRESENTER - Finch, Chris (Sport- és Egészségtudományi füzetek, 2025)
Accepting László Rátgéber’s invitation to the IV. International Basketball Conference made me delighted. My objective as the Minnesota Timberwolves’ head coach was to present a fresh coaching philosophy to European basketball players. Everyone wants to win in sports that are competitive. In addition to coaching the professional basketball players to victory, a successful head coach serves as a mentor to help them reach their professional goals. This goes well beyond the players’ technical and physical training. It entails leading by example and providing mental, psychological, and lifestyle support. Top basketball players must physically and mentally perform at the highest level under intense pressure due to the demanding competition schedule, but mental health cannot be compromised in the name of achievement. Players must focus on developing their individual skills, which is aided by team self-control and incredibly straightforward, uncomplicated team communication. Having technical preparation boosts one’s confidence. The long playing season can be divided into manageable details to establish development points and goals that will serve as a concrete accomplishment that will inspire and provide the team as a whole. The National Basketball Academy in Pécs has world-class facilities! Not only is the infrastructure truly incredible – I have not seen anything like it in Europe – but the entire environment. It includes all the components required for an academic framework